The doctoral research abstracts Vol:2 2012 / Institute of Graduate Studies, UiTM - Universiti Teknologi MARA, Institute of Graduate Studies (Institute of Graduate Studies, 2012)
Foreword: Congratulations to Institute of Graduate studies on the conscientious efforts to publish yet another issue of the doctoral research abstracts. The second issue, I believe reflects IGS continuity in the pursuit of academic excellence in research following the inaugural publication during the 76th convocation ceremony. The publication epitomizes knowledge par excellence and marks UiTM acknowledgment and tribute to the 27 doctorates whose achievements we proudly celebrate. Doctoral researches transcend beyond academic achievements which launch doctorates wherever they want to go or whatever they want to do. It is indeed the beginning of a lifelong learning and merely not a milestone, but a stepping stone in the lives of doctorates. This issue features the PhD abstracts from across the faculties from the disciplines of science and technology, social science and humanities; and business and administration. May the Almighty guides us to the straight path, in our endeavor for academic excellence and grant us success in this world and the next.